2021
DOI: 10.1080/23311908.2020.1860186
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 responses among general people of Bangladesh: Status and individual view toward COVID-19 during lockdown period

Abstract: This cross-sectional study has evaluated the level of the COVID-19 response among the general people of Bangladesh through their COVID-19 basic knowledge, attitude and practice level to reduce the outbreak. A rapid selfadministered online survey was conducted during the COVID-19 lockdown period in Bangladesh. Convenience and snowball sampling technique were followed in this study. The online survey was open for all Bangladeshi general people whether they were infected or not. For this study, total 616 Banglade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 41 publications
4
43
2
Order By: Relevance
“…[14,22] Marital status wasn't a significant predictor of perceived COVID-19 risk in Abir et al's study in Bangladesh, [14] but it was found to be associated with high risk perception in a study in China. [24] Although few studies couldn't establish a relation between geographical location and risk perception, [7,25] urban residents of our study revealed a significantly lower perceived risk than rural residents. It is concerning because the prevalence of COVID-19 is higher in urban areas in Bangladesh, necessitating special attention when developing risk communication programs.…”
Section: Discussioncontrasting
confidence: 59%
“…[14,22] Marital status wasn't a significant predictor of perceived COVID-19 risk in Abir et al's study in Bangladesh, [14] but it was found to be associated with high risk perception in a study in China. [24] Although few studies couldn't establish a relation between geographical location and risk perception, [7,25] urban residents of our study revealed a significantly lower perceived risk than rural residents. It is concerning because the prevalence of COVID-19 is higher in urban areas in Bangladesh, necessitating special attention when developing risk communication programs.…”
Section: Discussioncontrasting
confidence: 59%
“…Bangladesh is in an unprecedented situation due to the overwhelming COVID-19 impact. General people were concerned about the socio-economic condition and the psychological impacts [ 7 , 8 ]. To manage the COVID-19 situation Government of Bangladesh took different initiatives from the very beginning of the transmission of the virus, which include banning all international flights, declaring obligatory quarantine for 14 days for people coming from outside of the country, deploying special forces, banning all types of mass gatherings, declaring lockdown of different areas, announcing restriction on inter-city or inter-district movement, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Cut-off scores were calculated to categorize the score (high, moderate, and low) based on the quartile values in the KAP score. Details of this method can be found somewhere in previous studies [27][28][29].…”
Section: Introductionmentioning
confidence: 99%